Referral reasons of type 2 diabetes patients from general practitioners to diabetes specialists: a cross-sectional observational study - Antonin Ludinard; Jan Chrusciel; Stephane Sanchez (BMC Primary Care)
Abstract Background Diabetes is a global public health concern. The follow-up of patients with diabetes is often undertaken by general practitioners (GPs), but referral rates to specialists show variations. The primary objective of this study was to describe the factors associated with the referral of type 2 diabetes patients from GPs to diabetes specialists. Methods An observational survey-based cross-sectional study was conducted with GPs practicing in France between 17 May 2023 and 13 July 2023. Physician characteristics, referral rate and attitudes towards referral were collected. Characteristics associated with frequent referrals were evaluated using a multivariable logistic regression model. Results A total of 325 GPs located in 52 departments (mean age 43 years) responded to the questionnaire. Most responding GPs were women (63%). Most GPs (76%) stated that they rarely or never referred their patients with type 2 diabetes to a diabetes specialist. The most frequent barrier to referral was delays in accessing a specialist (57%), and it was often cited both in the infrequent referral group (56%) and the frequent referral group (58%). In multivariable analysis, higher referral rates were associated with physician age (Odds Ratio OR per year 1.04, 95% Confidence Interval CI 1.01 to 1.07), diabetes care network membership (OR 2.81, 95% CI 1.15 to 6.88), referrals motivated by the introduction of insulin therapy (OR 2.73, 95%CI 1.44 to 5.34) or to consolidate communication about therapeutics and compliance (OR 2.34, 95%CI 1.18 to 4.67), expecting advice regarding new medication such as SGLT-2 inhibitors (OR 2.08, 95% CI 1.11 to 3.98), and the mention of patient refusal as one of the main barriers to referral (OR 1.85, 95% CI 1.03 to 3.38) were associated with higher referral rates. Conversely, doubts about the added value of the diabetes specialist was associated with infrequent referrals (OR 0.25, 95% CI 0.08 to 0.66). Conclusions These factors indicate a possible role for lasting professional relationships, where trust built over shared network memberships and years of practice can facilitate referrals. Newly established GPs may find it beneficial to contact specialists in their region to discuss referral procedures. This could facilitate the referral of patients and improve access to specialist care.